Noninvasive positive pressure ventilation as treatment for acute respiratory failure in critically ill patients - Antonelli, Massimo (BioMed Central, 2000)
Our current state of knowledge on noninvasive positive pressure ventilation (NPPV) and technical aspects are discussed in the present review. In patients with chronic obstructive pulmonary disease, NPPV can be considered a valid therapeutic option to prevent endotracheal intubation. Evidence suggests that, before eventual endotracheal intubation, NPPV should be considered as first-line intervention in the early phases of acute exacerbation of chronic obstructive pulmonary disease. Small randomized and non-randomized studies on the application of NPPV in patients with acute hypoxaemic respiratory failure showed promising results, with reduction in complications such as sinusitis and ventilator-associated pneumonia, and in the duration of intensive care unit stay. The conventional use of NPPV in hypoxaemic acute respiratory failure still remains controversial, however. Large randomized studies are still needed before extensive clinical application in this condition.